EFFECT OF FARMERS- HERDSMEN CONFLICTS ON FOOD PRODUCTION IN OGUN STATE, NIGERIA (A CASE STUDY OF CASSAVA FARMERS) - Ogunwede, O. A.; Ochi, J.E.; Jibril, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the impact of farmers-herdsmen conflicts on food production among cassava farmers in Ogun State, Nigeria. A multi-stage sampling procedure was used in selecting 365 cassava farmers and 75 herdsmen for the study. Data were collected through structured questionnaires using a five-point Likert scale. Data were analyzed using descriptive statistics and Ordinary Least Squares (OLS) regression model. The study highlights a demographic predominance of older, married male farmers, indicating that these groups bear the brunt of the crisis. The effects of conflict variables—including loss of farm produce (-0.336), displacement of farmers (-0.197), and income lost by farmers (-0.094))—on food insecurity among respondents. The findings reveal that persistent conflicts have led to significant destruction of farmlands, loss of produce, displacement of farmers, and increased food scarcity, thereby undermining food security in Ogun State. The study concluded that the significant effect of farmers-herdsmen conflict in the study area were loss of farm produce, displacement of farmers and income loss by farmers, all of which undermine the livelihoods of rural households and threaten overall food security in the region. The predominance of older, married male respondents highlights the demographic most affected by these crises, while the gender imbalance in agricultural roles further complicates the socio-economic consequences of the conflict. Therefore, the study underscores the urgent need for effective conflict resolution mechanisms and policy interventions to address the root causes of farmers-herdsmen clashes in Ogun State. Without concerted efforts to foster peaceful coexistence and protect agricultural assets, the ongoing conflict will continue to erode food production capacity, exacerbate poverty, and hinder sustainable development in the region. Also, there is need for collaborative action among stakeholders—government, community leaders, and security agencies—to implement lasting solutions that ensure both food security and social harmony.